Energy conservation for production of 100,000 mt/a isobutylene plant and effect to the plant economic - Noor Adila, Zulkepa (2010)
This research shows how the application of Pinch technology can lead towards great energy saving. A few step need to undergo before start a heat exchanger network design which, analysis of process flow diagram data, pinch analysis and economic analysis. The heat exchanger network of the isobutylene process plant has been studied and it was shows how the application of pinch technology makes it possible to reduce the demand of hot and cold utility. After design the heat exchanger network, the overall heat exchanger required in these process is seven heat exchanger and all of them need to be redesign. The energy saving for total cooling is 65% and for total heating 38% which mean the good investment. Heat recovery is slightly reduced as the different minimum temperature increase. Even though the value of capital investment is higher than original process, but by implement pinch analysis in this plant, energy saving for utilities can recover the capital investment. Pay back period for the project is 0.8 year ( 9 month 3 days) that means, this project can be classify as quick win project